PRAKTIK PEMBUATAN ABON IKAN GUNA MENINGKATKAN PEMBERDAYAAN EKONOMI MASYARAKAT DESA SEBONG PEREH - Alamsyahbana, M. Isa; Fidianto, Angga; Yanti, Artika Rahma; Septira, Dewani; Fitriani, Dila; Sukmawati, Maulana Mega Putri Dwi; Muhawiyah, Siti (P3M STIE Pembangunan Tanjungpinang, 2025)
Desa Sebong Pereh Village is a coastel located in kecamatan Teluk Sebong, Bintan Utara, Provinsi Kepulauan Riau. The majority people in Sebong pereh village work as fishermen , who have various potentials from marine products. One potentials that stand out and can be exploited easily in the village is the catch of fishermen such as animal sea. In order to increase the economic value of a product, the fish can be made into a processed product so that is has a higher selling price compared to raw fish. Shredded meat is a healthy and long – lasting food that has hight protein and low cholesterol levels If the process all the best the aim shredded fish is to develop the potential of Desa Sebong Pereh from fishermen’s catches , produce nutrient and protein – dense, long – lasting food products, and open new bussines areas in order to improve the economy of the Desa Sebong Pereh Community.